TRAIN TICKETS RESERVATION SYSTEM IN THE COMPANY COMMON RAIL USING MICROSOFT VISUAL BASIC 6.0 - Rini Lesnarawati (Jurnal Sistem Informasi, 2005)
Railway ticket reservation system at the Railway Company is still done manually, the data is processed in such a complexity of customer data processing, calculation of costs and preparing reports. Along with the development of more advanced computers and sophisticated very helpful in data processing, so it can assist in providing accurate information, the information provided can be readily provided as a report to the CEO, which it will be very difficult for us to do if we still use the system manually. To make the application can use high level programming language like Microsoft Visual Basic is easy and provides facilities that can be used in making an application.Reservation system reservation system is especially important, because it was used as a report to the CEO of one-month immersion.